Pharmaceutical removal at low energy consumption using membrane capacitive deionization. (August 2021) - Son, Moon; Jeong, Kwanho; Yoon, Nakyung; Shim, Jaegyu; Park, Sanghun; Park, Jongkwan; Cho, Kyung Hwa
Abstract: The performance of the membrane capacitive deionization (MCDI) system was evaluated during the removal of three selected pharmaceuticals, neutral acetaminophen (APAP), cationic atenolol (ATN), and anionic sulfamethoxazole (SMX), in batch experiments (feed solution: 2 mM NaCl and 0.01 mM of each pharmaceutical). Upon charging, the cationic ATN showed the highest removal rate of 97.65 ± 1.71%, followed by anionic SMX (93.22 ± 1.66%) and neutral APAP (68.08 ± 5.24%) due to the difference in electrostatic charge and hydrophobicity. The performance parameters (salt adsorption capacity, specific capacity, and cycling efficiency) and energy factors (specific energy consumption and recoverable energy) were further evaluated over ten consecutive cycles depending on the pharmaceutical addition. A significant decrease in the specific adsorption capacity (from 24.6 to ∼3 mg−NaCl g −1 ) and specific capacity (from 17.6 to ∼2.5 mAh g −1 ) were observed mainly due to the shortened charging and discharging time by pharmaceutical adsorption onto the electrode. This shortened charging time also led to an immediate drop in specific energy consumption from 0.41 to 0.04 Wh L −1 . Collectively, these findings suggest that MCDI can efficiently remove pharmaceuticals at a low energy demand; however, its performance changes dramatically as the pharmaceuticals are present in the target water. Graphical abstract: Image 1 Highlights: The performances of the MCDI system were evaluated during pharmaceutical removal. Neutral APAP, cationic ATN, and anionic SMX were tested. Neutral APAP was removed ∼68% while ionic ATN and SMX were removed >93%. A significant decrease in SAC and SC were observed. The shorter operation time of the pharmaceutical addition led to lower SEC and E R .